Patient-Reported Symptom Relief Following Medical Cannabis Consumption - Stith, Sarah S.; Vigil, Jacob M.; Brockelman, Franco; Keeling, Keenan; Hall, Branden (Frontiers in Pharmacology, 2018)
Background: The Releaf AppTM mobile software application (app) data was used to measure self-reported effectiveness and side effects of medical cannabis used under naturalistic conditions. Methods: Between 5/03/2016 and 12/16/2017, 2,830 Releaf AppTM users completed 13,638 individual sessions self-administering medical cannabis and indicated their primary health symptom severity rating on an 11-point (0-10) visual analogue scale in real-time prior to and following cannabis consumption, along with experienced side effects. Results: Releaf AppTM responders used cannabis to treat myriad health symptoms, the most frequent relating to pain, anxiety, and depressive conditions. Significant symptom severity reductions were reported for all the symptom categories, with mean reductions between 2.8 and 4.6 points (ds ranged from 1.29-2.39, ps<0.001). On average, higher pre-dosing symptom levels were associated with greater reported symptom relief, and users treating anxiety or depression-related symptoms reported significantly more relief (ps<0.001) than users with pain symptoms. Of the 42 possible side effects, users were more likely to indicate and showed a stronger correlation between symptom relief and experiences of positive (94% of sessions) or a context-specific side effects (76%), whereas negative side effects (60%) were associated with lessened, yet still significant symptom relief and were more common among patients treating a depressive symptom relative to patients treating anxiety and pain-related conditions. Conclusions: Patient-managed cannabis use is associated with clinically significant improvements in self-reported symptom relief for treating a wide range of health conditions, along with frequent positive and negative side effects.